Performance of New Superior Variety of Rice and its Feasibility in Rainfed Rice Lowland of South Sumatra - Yeni E Maryana; Herwenita Herwenita; Y Hutapea (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2021)
Rainfed lowland has great potential to produce rice in South Sumatra Province. Rice cultivation in such marginal lowland needs technological innovation for sustainable use. This study aimed to analyze the crop performance and farming feasibility of a New Superior Variety (VUB) in rainfed rice cultivation. The study was carried out on 2019/2020 in Tugu Jaya Village, Lempuing District, OKI Regency. It was implemented in a demonstration plot of rice cultivation covering 2 hectares, using Inpari 30 and 43 varieties. The plant spacing was in accordance with 2:1 “jajar legowo” planting system. This was compared to the tile planting system outside the demonstration plot using IR 42 variety, which was planted by the local farmers. The results of observations of plants’ performance one day before harvest showed that the tallest plant was IR 42 (109.1 cm), the most tillers were from Inpari 43 (19.7 tillers), the longest panicle was of IR 42 (25.1 cm) and the highest harvested crop grain production was from Inpari 30 (6.8 tonnes/ha). In terms of business feasibility, judging from the resulting production and financial indicators, all three varieties were suitable for planting in rainfed lowland. Furthermore, of the three varieties, Inpari 30 on MH 2019/2020 was the most feasible, with a break-even price (BEPr) of Rp. 3,983 per kg; break-even production (BEP) of 1,568 kg per hectare; revenue cost ratio (R/C) of 2.39 and Marginal Benefit-Cost Ratio (MBCR) of 6.96.